Potential advancement utilizing nanotechnology-based delivery system to enhance the therapeutic properties of lavender essential oil: a review article - Trianloka, A. M. Bagas; Chabib, Lutfi; Ramadani, Arba Pramundita (Jurnal Ilmiah Farmasi, 2024)
Background: Essential oils (EO), such as lavender (Lavandula spp.), which are derived from its flower, have become a growing trend in recent years as an alternative medicine in therapy. However, the poor physicochemical properties of EOs have several disadvantages for their application. Integrating nanotechnology into the formulation of medicinal dosage forms may provide a viable way to mitigate these limitations and improve the effectiveness of EO utilization.Objective: This literature review aims to gather information on the medicinal benefits of lavender EO and the prospective applications of nanotechnology-based delivery systems for EOs.Method: Online databases such as PubMed, Science Direct, Research Gate, Google Scholar, and other reliable sources were used to find 65 publications between 1991 and 2021, which are assessed in this review.Results: It is revealed that the main constituents of lavender EO are linalool, linalyl acetate, and lavandulyl acetate. Its effectiveness as an antibacterial, antioxidant, anticancer, anti-anxiety, and having effects on the central nervous system, along with other qualities including pain relief, has been demonstrated via numerous studies. Additionally, it was demonstrated to have dermatological properties that helped treat dermatitis and encouraged both hair growth and wound healing. Furthermore, it was also found that the application of nanotechnology in EOs has improved the concentration of active compounds in the blood and produced a stable dosage form while also increasing its efficacy.Conclusion: It is feasible to create nanoparticle dosage forms from lavender EO that can improve the substance's solubility, stability, and pharmacological effects. More research is necessary to formulate lavender EO by applying nanotechnology.